Norway versus the European Union: Privileged partnership, outsider’s integration or selective co-operation? (Economic and Political Thought, 2016)
Norwegian historical, cultural and geopolitical ties with Europe have neverbeen questioned. The fate of this Nordic country, despite the geographicalconditions, made it have a unique status of an outsider among friends, i.e.the European Union countries. The close economic and political ties are putinto practice mainly in the framework of bilateral agreements and throughthe structure of the European Free Trade Association. The most importantagreement regulating economic relations between Norway and the EU isthe Agreement on the European Economic Area, which requires that thecountry implement the EU legislation concerning the internal market. Oneshould be aware that the status of Norway is mainly determined by thecharacteristic model of its economy. The country ranks among the richestcountries in the world and, what is more important, its prosperity is largelybased on export sales of energy resources – which Norway wants to controlindependently. This is the main reason why the country has not become anofficial member of the European Union structures. The idea has been rejectedin a referendum twice. Norwegians are still very Eurosceptic. Norwegianpolitical approach towards the European Union is often compared to theso-called ‘cherry picking’, which means implementing only the provisionsthat remain comfortable. However, cooperation is defined as a privilegedpartnership, and official documents describe Norway as a country integratedwith the EU at a rate of 75%.